2020
DOI: 10.1021/acs.orglett.0c02172
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Method for the Generation and Interception of 1,2-Cycloheptadienes with 1,3-Dipoles

Abstract: 1,2-Cycloheptadiene is a strained, transient species that has been underutilized as a synthetic building block. Sevenmembered cyclic allenes are mostly known for their propensity to undergo rapid dimerization, and relatively little has been reported regarding their cycloaddition reactivity with 1,3-dienes or 1,3-dipoles. This work describes the trapping of 1-acetoxy-1,2cycloheptadiene and its unsubstituted counterpart, generated via desilylative elimination, with a range of 1,3-dipolar trapping partners, affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“… 177 , 178 Subsequently, our laboratory and West’s laboratory expanded the synthetic utility of Kobayashi cyclic allene precursors to encompass other intermolecular cycloadditions, especially (3 + 2) cycloadditions. 179 182 …”
Section: Use Of Strained Cyclic Allenes To Access Polycyclic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“… 177 , 178 Subsequently, our laboratory and West’s laboratory expanded the synthetic utility of Kobayashi cyclic allene precursors to encompass other intermolecular cycloadditions, especially (3 + 2) cycloadditions. 179 182 …”
Section: Use Of Strained Cyclic Allenes To Access Polycyclic Scaffoldsmentioning
confidence: 99%
“…Whereas arynes and strained cyclic alkynes have been studied extensively, a related counterpart, strained cyclic allenes (i.e., 4 , 93 – 94 , Figure ), have received significantly less attention. Of note, the discovery of 1,2-cyclohexadiene ( 4 ) by Wittig was reported in 1966, only 9 years after the validation of cyclohexyne (and 13 years after the validation of benzyne in 1953). ,, Theoretical investigations of these species have been reported as well as synthetic advances, most notably by Christl. In a key finding, Guitián and co-workers developed Kobayashi precursors to strained cyclic allenes and demonstrated their utility in several transformations, such as [4 + 2] cycloadditions. , Subsequently, our laboratory and West’s laboratory expanded the synthetic utility of Kobayashi cyclic allene precursors to encompass other intermolecular cycloadditions, especially (3 + 2) cycloadditions. …”
Section: Use Of Strained Cyclic Allenes To Access Polycyclic Scaffoldsmentioning
confidence: 99%
“…In 1983, Kobayashi and co‐workers developed 14e a captivating synthetic route for a slow generation of aryne by reacting benzyne precursor o ‐(trimethylsilyl)phenyl triflate [C 6 H 4 (TMS)(OTf)] with fluoride ion (F − ) in solution (MeCN/toluene). This fluoride (CsF or NH 4 F)‐mediated elimination of TMS and OTf groups (as F−TMS and CsOTf) from aryne [Ar(TMS)(OTf); TMS = SiMe 3 , OTf = O 3 SCF 3 ] leading to the formation of reactive aryne has become a more accomplished milder synthetic route in the recent past (Scheme 1; Top) 14c–e,16–27 . Very recently, the utility of Kobayashi aryne [Ar(TMS)(OTf)] 14e has been thoroughly summarized by Li et al, displaying all possible ways how this class of precursors have been utilized for the syntheses of different classes of organic compounds 14c,d .…”
Section: Introductionmentioning
confidence: 99%
“…The C Ar Si bond (Ar = pyridine, 1,3-benzodioxole) bond is electrostatic in nature, while indoleOTfÀSiMe 3 bond is covalent (TableS6). Nevertheless, Apart from the different classes of aryne precursors discussed, we carried out bonding analysis on ArOTf(X) SiMe 3 (X = OMe 2 (21), Me 2(22), and OTf(23); Ar = benzene) class of precursors(21)(22)(23)…”
mentioning
confidence: 99%
“…However, to date, only three major intermolecular reaction classes have been reported for these intermediates (Figure B), the most frequently studied being nucleophilic trappings (e.g., 7 + KO t- Bu → 6 ) and cycloadditions (e.g., 7 + 8 → 9 ) . More than 50 studies detailing such reactions have been reported, including more recent studies by Guitián, , West, Okano and Mori, , Schreiber, and our laboratory. A complementary, albeit rarely studied, approach utilizes transition metal catalysis to intercept the cyclic allene (e.g., 7 + 10 → 11 ). , However, this strategy poses an inherent kinetic challenge due to the requirement for reaction between a catalytically generated intermediate and an in situ generated fleeting cyclic allene, both of which are present in low concentration.…”
mentioning
confidence: 99%